Understanding Multicultural-Based Islamic Education - Hamid A.Ghani, Sulhan (Jurnal Paradigma, 2021)
In a pluralistic society there are various groups of people who have different backgrounds; culture, customs, interests, language, arts, beliefs and religion, which usually face challenges of disharmony in common life and have great potential for conflict between groups; Race, Ethnicity and Religion. Conflicts with religious nuances often collaborate strongly with non-religious factors. Islam as the religion of the majority of the population in the Republic of Indonesia plays a very important role in creating an atmosphere of life full of harmony and mutual respect. In realizing this, it is necessary, among others, to carry out Islamic Religious Education with a multicultural perspective. Therefore, this study seeks to "Understand Multicultural-Based Islamic Education." Based on the study conducted, it can be concluded that Islamic Religious Education is Education in which all aspects and components are based on Islamic teachings, while Multicultural Education is a learning strategy that is applied to all types of subjects by setting cultural differences that exist to students. From the results of the discussion, it can be assumed that the material for Islamic Religious Education contains many teachings with multicultural nuances. This can be found, for example, in the texts of the verses of the Qur'an or the Hadith of the Prophet Muhammad SAW, which contain messages that should serve as guidelines for mankind in an effort to maintain harmony, peace and tolerance in the life of a nation and a state that is full of multiculturalism, such as in the Republic of Indonesia.